PERTANGGUNGJAWABAN HUKUM DOKTER PROGRAM INTERNSIP DALAM PELAYANAN KESEHATAN TERHADAP PASIEN - Ade Irwanto; Fakhruddin Razy (Audito Comparative Law Journal (ACLJ), 2021)
.  Suppose there is a problem related to the loss incurred to the patient when the doctor of the Internship program does not meet the established educational standards. In that case, health services will be exposed to a greater risk of civil liability if they ignore internal arrangements related to internal physicians. The risk of joint civil litigation will be very burdensome for interns and hospitals if hospital leaders issue wrong clinical assignments. Hospitals need to be aware that material and substance cannot be compared between hospitals and hospitals. Each hospital should ask their medical committee to arrange bylaws related to implementing the profession of interns in their respective hospitals. The approach used in this study is the method of the Legislative Approach (Statue Uproach), Conceptual Approach, and Sociological Approaches. By law anyone who causes or incurs a loss to another person is required to account for any such loss. Likewise, doctors, as health workers who have provided health services (medical measures) to patients, if the doctor incurs losses with these services, are obliged to provide accountability. The responsibility of doctors who commit malpractice can be punched in 3 (three) aspects: civil, criminal, and administrative matters.